#TITLE_ALTERNATIVE# - NURSYAHBANI (NIM : 10109021) Pembimbing : Dr. Nuning Nuraini, AWALIA
Women experienced cycle of menstruation every month. Before the menstruation phase comes, we call the phase before it as pre-menstruastion phase. In this pra-menstruation phase there are symptoms that influence women as physically or emotionally. One of the symptoms is rapid change of mood in women. In here we will discuss about dynamics model of mood and its relation to pre-menstruation on women. Assume that only Estrogen dan Serotonin will influence the mood on women. This model is an adaptation of Newton’s Second Law of Motion and Spring-Mass System with Damping Equation. From the model will be done some general mood simulation in normal condition and in pre-menstruation phase. Some simulation also will be made from mood graphics data of samples which are female student of Mathematics’ major 2009 in Bandung Institute of Technology. The value of b representates level of Estrogen per day and w2 representates the velocity of level changes in Serotonin per day. The value of b and w2 can predict sample’s mood dynamics and their individual character. However, the pra-menstruation phase doesn’t always affect the mood on samples. External factors and individual character have more influence on mood. From the simulation, sample which is selected uniquely, Sanguine has positive mood but fluctuative with b = 0:8 dan w2 = 6. Cholerics has positive and stable mood with b = 0:5 dan w2 = 2. Phlegmatics has positive and stable mood with b = 0:045 dan w2 = 3:9. Melancholy has negative mood and stable mood with b = 0:05 dan w2 = 2.